Análisis de los modelos pedagógicos que inciden en el proceso de enseñanza aprendizaje en el área de cultura física en la unidad educativa monseñor “Alberto Zambrano Palacios” del cantón Olmedo, provincia de Loja en el periodo 2013-2014 - Robles Robles, Manuel Alfredo (2014)
The fundamental purpose of the investigation and in accordance with the objectives and specific hypotheses are geared to meet on the analysis of pedagogical models that influence the teaching-learning process of the College Bishop Alberto Zambrano Olmedo Canton province of Loja. The specific objectives that were raised in this research are aimed to analyze whether Models Pedagogical in Process Teaching Learning used by teachers in the area of Physical Culture , facilitate the achievement of significant learning in students of the United Educative Monsignor " Alberto Zambrano Palacios" and know if the lack of training of teachers of Physical Culture , limited Pedagogical Models in the Teaching Learning process of Physical Culture in College students Fiscomisional Monsignor " Alberto Zambrano Palacios" Olmedo canton , Province of Loja. The structure of the thesis is described as follows in paragraph ( a) refers to the title of Research , in paragraph ( b ) the summary in Castilian and English is exposed , in paragraph ( c ) introduction describes investigative work in paragraph ( d ) review of the literature related to the variables to paragraph (e ) methodological process carried out for the realization of research taking into account the design of research materials used , methods , population and sample. In paragraph ( f ) the results of the survey of teachers and students in paragraph ( g ) detailed discussion for the verification of the hypothesis is made , paragraph ( h ) of the research findings are presented , in ( i ) the recommendations described , in paragraph ( j) finds the literature and finally paragraph ( k ) corresponds to the attachments section and in the draft and approved the list of contents.